2016
DOI: 10.4028/www.scientific.net/msf.846.395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Variation Sintering Temperature on Magnetic Permeability and Grain Sizes of Y<sub>3</sub>Fe<sub>5</sub>O<sub>12</sub> via Mechanical Alloying Technique

Abstract: This work will focus on the preparation of yttrium iron garnet (Y3Fe5O12, YIG) via mechanical alloying technique derive by steel waste product. The Fe2O3 powder derived from the steel waste purified by using magnetic and non-magnetic particles (MNM) and Curie temperature separation (CTS) technique. The purified powder was then oxidized in air at 500 °C for 9 hours in air. The Fe2O3 was mixed with Y2O3 using high energy ball milling for 9 hours. The mixed powder obtained was pressed and sintered at different te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…As illustrated in Figure 1, the mill scale flakes were crushed into coarse powder and purified, using the magnetic separation methods described in Refs. [5,8], to obtain the magnetic wustite (FeO) slurry that was then filtered and dried in a Memmert drying oven for 24 h at 30 °C. The dried FeO was then oxidized in a Protherm furnace at 600 °C for 6 h (holding time) to produce the α-Fe 2 O 3 powder.…”
Section: Methodsmentioning
confidence: 99%
“…As illustrated in Figure 1, the mill scale flakes were crushed into coarse powder and purified, using the magnetic separation methods described in Refs. [5,8], to obtain the magnetic wustite (FeO) slurry that was then filtered and dried in a Memmert drying oven for 24 h at 30 °C. The dried FeO was then oxidized in a Protherm furnace at 600 °C for 6 h (holding time) to produce the α-Fe 2 O 3 powder.…”
Section: Methodsmentioning
confidence: 99%
“…The mill scale flakes were crushed into coarse particles and purified using magnetic and curie separation techniques [8,9]. The wustite (FeO) slurry produced was filtered, dried and oxidized at 600 °C for 6 h (holding time) in a Protherm furnace to obtain the recycled α-Fe 2 O 3 which was then milled.…”
Section: Methodsmentioning
confidence: 99%
“…Among the less extensively used ferrites for microwave absorption applications is hematite (α-Fe 2 O 3 ), a ferrite (corundum-type oxide) which is stable under ambient conditions with unique electrical and magnetic properties. Recently, α-Fe 2 O 3 was successfully synthesized from industrial mill scale waste material [8,9] through a low-cost technique. Recycled α-Fe 2 O 3 is cheap, reduces environmental pollution and its generally low dielectric loss properties [10] can be enhanced by reducing the particles to the nanosize for use in polymer composites for microwave absorption applications.…”
Section: Introductionmentioning
confidence: 99%
“…The micrograph of the sample sintered at 500, 600, and 700°C revealed that the sample encounters initial stage of sintering. The initial stage of sintering involves rearrangement of the powder particles and formation of strong bond or necks at the contact point between particles [8]. At 500 and 600°C, the sample showed nearly the same evolution trend, where the sample sintered at 500-600°C showed slight particle growth and rearrangement of the particles.…”
Section: Mss Of Yttrium Iron Garnet (Yig)mentioning
confidence: 98%